Strategi Pembelajaran Fiqh Munakahat dengan Pendekatan Deep Learning di MA Fatihul Ulum Prajjan Camplong Sampang - Ismail, Ismail (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to analyze the implementation of the Deep Learning approach in the teaching of Fiqh Munakahat at MA Fatihul Ulum Prajjan Camplong Sampang. This approach is examined as a strategy to create meaningful learning that promotes higher order thinking skills. The research employs a descriptive qualitative method with educational phenomenology design. The findings indicate that Deep Learning in Fiqh Munakahat is implemented through curriculum integration based on the Ministry of Religious Affairs Decree No. 183 of 2019, enriched by classical Islamic texts such as Fath al-Qarib and Bidayat al-Mujtahid, and expanded with contemporary social themes including child marriage, online marriage, and women’s rights in Islam. The instructional strategies include Problem-Based Learning, Inquiry Learning, and Reflective Dialogue, which foster cognitive engagement and spiritual reflection. Teachers also employ the maqāṣid al-Sariah framework to help students grasp the moral and social purposes behind each legal ruling. Authentic assessment methods—contextual tests, group projects, and reflective journals—replace rote memorization with competency-based evaluation. The application of Deep Learning significantly enhances students’ legal analysis skills, critical awareness of contemporary issues, and moral-spiritual maturity. Consequently, this approach contributes innovatively to developing Fiqh Munakahat instruction that is meaningful, contextual, and character-building.